1995
DOI: 10.1042/bj3060199
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of calponin with actin and its functional implications

Abstract: Titration of F-actin with calponin causes the formation of two types of complexes. One, at saturation, contains a lower ratio of calponin to actin (0.5:1) and is insoluble at physiological ionic strength. The another is soluble, with a higher ratio of calponin to actin (1:1). Electron microscopy revealed that the former complex consists of paracrystalline bundles of actin filaments, whereas the latter consists of separate filaments. Ca(2+)-calmodulin causes dissociation of bundles with simultaneous increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 39 publications
5
56
0
Order By: Relevance
“…At intermediate ionic strength (10 mM Tris/acetate, pH 8.3, 30-50 mM NaC1) the apparent dissociation constant increased up to 11-15 ~tM and the stoichiometry became equal to 1 mol calponin per 4-6 mol desmin. Thus, the stoichiometry of the calponin~tesmin complex is similar to that of calponin-actin (1 calponin/2~, mol target protein) and affinity of calponin to desmin is 10-100 times lower than that to actin [2,9,24,25]. Nevertheless, taking into account rather high content of both calponin and desmin in smooth muscle (= 130-150 pM for both proteins) [22,24], desmin-calponin interaction may be of physiological significance.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…At intermediate ionic strength (10 mM Tris/acetate, pH 8.3, 30-50 mM NaC1) the apparent dissociation constant increased up to 11-15 ~tM and the stoichiometry became equal to 1 mol calponin per 4-6 mol desmin. Thus, the stoichiometry of the calponin~tesmin complex is similar to that of calponin-actin (1 calponin/2~, mol target protein) and affinity of calponin to desmin is 10-100 times lower than that to actin [2,9,24,25]. Nevertheless, taking into account rather high content of both calponin and desmin in smooth muscle (= 130-150 pM for both proteins) [22,24], desmin-calponin interaction may be of physiological significance.…”
Section: Resultsmentioning
confidence: 96%
“…On one hand, calponin has been deduced to play a role in the regulation of smooth-muscle contraction [2,5,7]. On the other hand, the low efficiency of calponin in inhibition of actomyosin ATPase [8,9] and its wide distribution in nonmuscle tissues (such as brain, fibroblasts and platelets) [2,4,10] may indicate that calponin is not only involved in regulation of the actomyosin system but also has other functions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CaP at high concentrations can induce bundles of smooth muscle F-actin (23). When smooth or skeletal muscle F-actin were incubated together with UNC-87 and centrifuged for 20 min at 18,000 ϫ g, actin and UNC-87 were found together in the low speed pellet, indicating the induction of actin bundles by UNC-87 (Fig.…”
Section: Expression and Purification Of Recombinant Unc-87-thementioning
confidence: 91%
“…Their interaction with actin filaments is an essential condition for the regulation of the actin-myosin machinery [1,2]. Calponins consist of a unique N-terminal domain followed by one to three calponin repeats.…”
Section: Introductionmentioning
confidence: 99%